Barofeedback - Sanjay Kalra; Nishant Raizada; Sourabh Sharma; Nitin Kapoor (Journal of the Pakistan Medical Association, 2026)
Obesity is a complex and challenging disease, which needs both behavioural and medical therapy for management. We suggest the term barofeedback for use in obesity treatment. Barofeedback is a comprehensive biopsychosocio-environmental approach, which uses information gained from awareness of external cues and triggers, subjective internal responses, and objective physiological parameters, to assist the individual and their caregivers in modification and optimization of attitudes, behaviours and choices related to weight management. This concept should be integrated in all obesity care protocols. Keywords: GLP1RA, obesity, overweight, psychosocial weight management, behavioural therapy.